Pseudoprogression and hyperprogression secondary to immunotherapy in lung cancer - R. Riera-Sala; A. Ibarra-Morales; J. Guzmán-Casta; R. Medrano-Guzmán; A. Dip-Borunda; A. Martin-Aguilar; R. Grajales-Álvarez; R. Correa-Cano; K. Elvira-Fabián; C. Sánchez-Ríos; A. Orzuna-Vázquez; J. Rovelo-Lima; et al. (World Cancer Research Journal, 2023)
BACKGROUND: The treatment of non-small cell lung cancer (NSCLC) has undergone changes that have improved the prognosis of patients. With the advent of immunotherapy, it has been possible to prolong significantly the overall and progression-free survival as well as quality of life. Nevertheless, its use represents clinical challenges which may turn into adverse events, such as progression and pseudo-progression, which are uncontrolled and often deleterious immune responses that simulate tumoral progression, generate worsening of symptoms and performance status of patients and even may lead to non-cancer related death of patients. MATERIALS AND METHODS: We assessed 128 records (clinical trials, reports, meta-analyses) in order to provide an updated review of the treatment of NSCLC, current definitions proposed for pseudo and hyperprogression (which are not homogeneous so far), incidence, theories about their physiopathogenesis, importance of making a judicious diagnostic workup, imaging criteria as well as biochemical markers in order to predict their appearance, concluding with a brief discussion about the topic addressed. CONCLUSIONS: Since there is no definition or standardized diagnostic and imaging criteria, these entities are a topic of major interest in the area of oncologic immunotherapy, for which the following review has been generated.